Wamicon 2014 2014
DOI: 10.1109/wamicon.2014.6857806
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on RSS-based wireless localization with software defined radio

Abstract: Wireless localization has been an active research area over the last decade due to its endless applications. In this paper, we investigate received signal strength (RSS) based estimation of a mobile station's location, through monitoring the RSS at multiple reference software defined radio (SDR) receivers. Uplink transmission power of the mobile stations and path loss exponent are assumed to be unknown parameters. Universal software radio peripheral (USRP) devices are used to capture the RSS from uplink transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…This is the well-known trilateration problem. There are many sources providing potential solutions as in [10], [12], [25], [26]. For the sake of completeness of this study, we present the detailed solution as follows: representing the system in matrix form (A. m = b) as [25]:…”
Section: A Multilateration Solution For 3 Base Stationsmentioning
confidence: 99%
“…This is the well-known trilateration problem. There are many sources providing potential solutions as in [10], [12], [25], [26]. For the sake of completeness of this study, we present the detailed solution as follows: representing the system in matrix form (A. m = b) as [25]:…”
Section: A Multilateration Solution For 3 Base Stationsmentioning
confidence: 99%
“…The corresponding loss function of the mirror layer decoded by the second hidden layer in (14) is then employed to converge the weights of the second layer of the denoising autoencoder, such that the second layer loss function is defined as:…”
Section: Deep Learning and Denoising Autoencodermentioning
confidence: 99%
“…The results documented localization performance of sub-0.5 m in an undocumented environment. Finally, the most recent research expressed in [14] demonstrated one of the first machine learning based WiFi localizing SDR platforms. The SDR leveraged simultaneous RSS and CSI in a LabVIEW aided system cascaded with a convolutional neural network to achieve approximately 1 m of localization error.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SDR has many applications in various fields, such as spectrum monitoring [ 19 ], RF transmitter identification [ 25 ], and other areas. For example, it was used as a receiver to estimate a mobile station’s location through received signal strength [ 26 ]. Bonoir et al applied SDR to remote wireless tomography in their experiment [ 27 ].…”
Section: Introductionmentioning
confidence: 99%